PERENCANAAN REHABILITASI KOLAM DETENSI MELATI JAKARTA PUSAT - Undayani Cita Sari; Evi Mariana; Suseno Darsono; Siti Hardiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
ABSTRACTDrainage system with polder and pump is the most effective and efficient system for handling the floods that was occurred in the area which has a slooping topography such as Jakarta. As the state’s capital and metropolitan city, Jakarta has been developing rapidly, which made the existing green land as water infiltration area and settlement become unbalanced. This is a major cause of flooding in Jakarta. From the result of rainfall data processing in Kemayoran station, rainfall intensity can be analyzed by using Jakarta’s hyetograph diagram approach for Ciliwung’s watershed based on analysis that was conducted by Netherland Engineering Consultant. Qplan is obtained by modeling it with additional program, the SWMM 5.0 for a period of 100 years, due to Jakarta as a business and government center. Large catchment area and downtown are the reason that SWMM 5.0 is suitable to use for modeling. Thus Qplan is obtained in the amount of 11 m3. Reservoir’s volume in the amount of 75888 m3 is obtained by using Qplan, at the existing condition detention pond area is 49000 m2, so depth of pond is 5 m with 8 pumps and 4 m3/sec capacity is obtained.